Canva sebagai Alat Bantu Visual dalam Pembelajaran Bahasa Arab: Review tentang Penguatan Pemahaman Struktur Jumlah Mufidah - Nurjannah Nurjannah; Ahmad Helwani Syafi'i; Ahmad Rosyidi; Fitriani Fitriani (Pendekar: Jurnal Pendidikan Berkarakter, 2025)
Abstract: The teaching of Arabic still faces challenges in mastering grammatical aspects, particularly the construction of jumlah mufidah (meaningful sentences), which forms the foundation of language skills. The use of interactive media such as Canva remains limited and has not been widely explored in relation to this specific aspect. This study aims to analyze the effectiveness of Canva in enhancing students’ ability to construct jumlah mufidah through a Systematic Literature Review (SLR) approach. Data were collected from three major databases Scopus, DOAJ, and Google Scholar covering publications from 2015 to 2025. The screening process yielded 32 articles that met the inclusion criteria, namely studies that examined interactive media in Arabic language learning or other foreign language contexts with a grammatical focus. Articles unrelated to interactive media, lacking a focus on grammar, or published outside the specified range were excluded. Data were analyzed thematically to identify Canva’s contribution to Arabic learning. The findings indicate that Canva is effective in improving: (1) accuracy in constructing jumlah ismiyah and jumlah fi’liyah, (2) students’ ability to select vocabulary according to syntactic function, (3) variety in sentence construction, and (4) students’ independence in composing meaningful sentences. Canva’s strengths lie in its ease of use, interactive visual features, and compatibility with Arabic text. Thus, integrating Canva represents a significant pedagogical innovation for Arabic language instruction, particularly in strengthening students’ mastery of core grammatical structures.Abstrak: Pembelajaran bahasa Arab masih menghadapi kendala dalam penguasaan aspek gramatikal, khususnya pembentukan jumlah mufidah yang menjadi dasar keterampilan berbahasa. Pemanfaatan media interaktif seperti Canva relatif terbatas dan belum banyak dikaji secara spesifik pada aspek ini. Penelitian ini bertujuan untuk menganalisis efektivitas Canva dalam meningkatkan keterampilan siswa membentuk jumlah mufidah melalui pendekatan Systematic Literature Review (SLR). Data dikumpulkan dari tiga basis utama, yaitu Scopus, DOAJ, dan Google Scholar, dengan rentang publikasi 2015–2025. Proses penyaringan menghasilkan 32 artikel yang memenuhi kriteria inklusi, yakni penelitian yang mengkaji media interaktif dalam pembelajaran bahasa Arab atau bahasa asing terkait tata bahasa. Artikel yang tidak relevan dengan media interaktif, tidak berfokus pada gramatika, atau di luar rentang tahun publikasi dikeluarkan dari analisis. Data dianalisis menggunakan pendekatan tematik untuk mengidentifikasi kontribusi Canva dalam pembelajaran bahasa Arab. Hasil kajian menunjukkan bahwa Canva efektif dalam meningkatkan: (1) ketepatan struktur jumlah ismiyah dan fi’liyah, (2) kemampuan memilih kosakata sesuai fungsi sintaksis, (3) variasi konstruksi kalimat, dan (4) kemandirian siswa dalam menyusun kalimat bermakna. Keunggulan Canva terletak pada kemudahan penggunaan, dukungan visual interaktif, serta keterpaduannya dengan teks Arab. Dengan demikian, integrasi Canva berpotensi menjadi inovasi penting dalam pembelajaran bahasa Arab, khususnya pada penguasaan struktur gramatikal inti.